Reduction of bubble coalescence by louver baffles in fluidized bed gasifier. (November 2022) - Phuakpunk, Kiattikhoon; Chalermsinsuwan, Benjapon; Assabumrungrat, Suttichai
Abstract: Bubble coalescence is a cause of decrease in gas–solid contact in a bubbling bed gasifier. This study used computational fluid dynamics (CFD) to explore a louver baffles arrangement that could reduce the bubble coalescence in the bubbling bed gasifier fueled by biomass. The results showed that 20 mm-gap baffles were not able to reduce the bubble coalescence while the 10 mm-gap baffles were effective to reduce the bubble size and slow down the bubble coalescence. The 10 mm-gap baffles also provided better gas–solid contact thorough the system. In addition, these baffles arrangement would steadily maintain full fluidization above the baffles.